THE STUDENTS OF PHYSICAL FITNESS OF IFTO (Fiep Bulletin - online, 2012)
The objective of this study was to assess the physical fitness of students at the Education, Science and Technology Federal Institute of Tocantins / IFTO - Campus Araguaína through the flexibility test (sit and reach), the strength test of abdominal endurance, test explosive strength of the lower limbs (horizontal jump), test explosive strength of upper limbs (pitch medicineball), the agility test (test of the square), the travel speed test (run 20 meters), the cardiorespiratory fitness test (9 minutes) and its comparison with the reference values proposed by Gaya and Silva (2007), classified as VERY LOW, LOW, REASONABLE, GOOD, VERY GOOD and EXCELLENCE. The study was a descriptive, the selection process was casual random type, descriptive statistics to characterize the groups according to sex, through measurements of location and dispersion. The sample analyzed in this study composed 24 students (10 masculine and 14 feminine), officially registered in the Education, Science and Technology Federal Institute of Tocantins – IFTO, Campus Araguaína – Brazil. The results for the flexibility of the students of the IFTO of both sexes allowed us to classify them within the category REASONABLE. The results for the agility and endurance of the students of the IFTO of both sexes allowed us to classify them within the category WEAK. The results for speed the students of the IFTO of males and females allowed us to classify them respectively within the category of very good and good. The results for the strength test of abdominal endurance of the students of the IFTO males and females allowed us to classify them respectively in the category VERY WEAK and WEAK. The results for explosive strength of upper and lower limbs of the students male of the IFTO allowed us to classify them respectively in the category GOOD and REASONABLE, and the results found for explosive strength of upper and lower limbs of the students female of the IFTO allowed us to classify them respectively in the category VERY GOOD and GOOD. This denotes a level of physical fitness of the students of the IFTO investigated within the desirable and compatible with a healthy lifestyle.
Keywords: students; physical fitness; health